Optimization of methyl cellulose biopolymer electrolyte conductivity via response surface methodology - Misenan, M. S. M.; Khiar, A. S. A. (ELSEVIER, 2024)
Optimization conductivity of methyl cellulose (MC) / ammonium triflate (NH4 CF3 SO3) / 1-butyl-3-methyl imidazolium bis (trifluoro sulfonyl) imide (BMIMTFSI) biopolymer electrolyte was carried out using response surface methodology (RSM) based on faced centred central composite design (FCCCD). This software was used to evaluate two different parameters simultaneously, which are the weightage of NH4CF3SO3 salt (40 - 50 w.t%) and BMIMTFSI ionic liquid (1 - 50 w.t%). Analysis of variance was used to verify the experiment data by using quadratic model. The value of R2 for this model was found to be 0.933526, hence showed that the model is significant. Electrochemical impedance spectroscopy (EIS) was used to calculate the conductivity (1.26 x10- 3 Scm-1) for 45 wt% NH4CF3SO3 salt and 30.7 w.t% BMIMTFSI ionic liquid and was found comparable to the predicted conductivity value (1.28 x10- 3 Scm- 1). The differences between these two values are less than 10%. Statistical observation from ANOVA analysis showed that, the weightage of NH4CF3SO3 salt and BMIMTFSI ionic liquid have significant effect to the conductivity of MC/NH4CF3SO3 / BMIMTFSI biopolymer electrolyte.
Keywords: Polymer electrolyte; Methyl cellulose; Ammonium triflate; Ionic liquid; Conductivity; POLYMER; PARAMETERS; IMPEDANCE; TRANSPORT; Chemistry; Materials Science